Epidemiological profile of violence against children and adolescents: an analysis of compulsory notifications in the State of Paraiba (Research, Society and Development, 2020)
The aim of this paper was to describe the epidemiological profile of violence against children and adolescents in the state of Paraiba. It was a descriptive, retrospective, quantitative and documentar study. The data used was collected from the Notifiable Diseases Information System (SINAN), registered in the state of Paraiba, between the years 2009 and 2017, involving the age group from 0 to 19 years and available in TabNet – Domestic, Sexual and/or Others Violence. The variables used were: year of registration, age and sex of the victim, type of violence perpetrated, place of occurrence of the fact and type of bond with the aggressor. It was found that the victim's sex and age group were associated (p